2006
DOI: 10.1007/s10519-006-9083-6
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of the Effects of a γ-protein Kinase C Null Mutation on Gene Expression in Striatum: A Role for Transthyretin in Mutant Phenotypes

Abstract: A constitutive null mutation of the neural-specific isotype of protein kinase C (gamma-PKC) in mice produces alterations in behavioral traits and responses to ethanol suggesting that gamma-PKC-mediated phosphorylation is essential for regulation of some behaviors. However, it is possible that some of the effects of gamma-PKC gene deletion also may be due to altered gene expression. To examine alterations in gene expression, microarray analyses were performed on striatal tissue from wild types and mutants. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 83 publications
(81 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, the similarities of DEGs (Prkcg, opioid signaling genes, Rassf5, potassium channel subunits, Lore QTL genes) and gene networks (MAPK signaling pathway, oligodendrocyte enrichment, Lore4 QTL enrichment) between this study and prior studies using other models of alcohol behaviors were noteworthy (Darlington et al 2013;Smith et al 2006). This led us to propose that wheel running induced an increase in sensitivity to ethanol, thereby decreasing ethanol consumption.…”
Section: Identification Of Candidate Genes Through Striatal Gene Exprsupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, the similarities of DEGs (Prkcg, opioid signaling genes, Rassf5, potassium channel subunits, Lore QTL genes) and gene networks (MAPK signaling pathway, oligodendrocyte enrichment, Lore4 QTL enrichment) between this study and prior studies using other models of alcohol behaviors were noteworthy (Darlington et al 2013;Smith et al 2006). This led us to propose that wheel running induced an increase in sensitivity to ethanol, thereby decreasing ethanol consumption.…”
Section: Identification Of Candidate Genes Through Striatal Gene Exprsupporting
confidence: 59%
“…A previous study of gamma-protein kinase c ( Prkcg ) showed the differences in ethanol consumption between null mutant and wildtype mice could be correlated with differences in the expression of transthyretin ( Ttr ) (Smith et al, 2006). While we previously showed a similar difference in Ttr expression between strains of mice selected for ethanol sensitivity, the current study does not support this.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genes from Lore QTL regions, transthyretin (Ttr) on chromosome 19 was also identified in both samples as being differentially expressed. Gamma-protein kinase C (PKC-γ ) null mutant mice and their wild-types have similar ethanol-related behaviors as the ISS and ILS mice, and these differences were correlated with baseline Ttr expression, which is higher in mutant mice (Smith et al 2006). Similar to the ISS mice, PKC-γ null mutants are less sensitive to acute ethanol than their wild-type littermates (Harris et al 1995), and voluntarily consume more ethanol (Bowers & Wehner 2001).…”
Section: Discussionmentioning
confidence: 99%
“…DNA microarray analyses on the PKCγ knockout mice show changes in activity towards transerythrin, a thyroxin and retinol transport protein [98]. In brain, PKCγ directly interacts with and phosphorylates the GluR4 alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionate receptor subunit [100].…”
Section: Substrate Specificity Of Pkcε and Pkcγmentioning
confidence: 99%